Enzymatic hydrolysis lignin and kraft lignin from birch wood: a source of functional bio-based materials - Huerta, Edgar Ramirez; Muddasar, Muhammad; Collins, Maurice N. (Wood science and technology, 2024)
In the pursuit of sustainable biomass utilization, this study investigates the hydrothermal treatment of birchwood and its subsequent impact on enzymatic hydrolysis lignin (EHL). Additionally, birchwood undergoes processing with NaOH (4% w/w) within a Parr reactor to precipitate lignin from the black liquor, resulting in lignin-rich substrates (LRSs) which are then subject to thorough characterization. Notably, EHL produced after hydrothermal pretreatment at 190 °C exhibits the highest lignin content at 67%, while kraft lignin (KL) obtained at 140 °C (pH 1.5) produces 65% lignin content. Among these LRSs, the KL sample produced at 190 °C (pH 4) stands out, displaying a robust aromatic skeletal structure and an abundance of methoxyl groups, primarily owing to its high purity. Furthermore, for these LRSs' it is shown that chemical configuration influences their thermal behaviour, allowing the lignin to be tailored for diverse applications, from low melting point materials to carbonaceous materials capable of withstanding temperatures exceeding 700 °C. This comprehensive understanding of the chemical, thermal, and physical attributes of LRSs not only enriches our knowledge of lignin-rich substrates but also paves the way for the development of sustainable bio-based materials, marking a step towards sustainable materials development.